令y/(x-1)=u,则:y=(x-1)u,∴dy/dx=u+(x-1)du/dx,
∴由(x-y-1)dx+(4y+x-1)dy=0,得:
[1-y/(x-1)]+[4+y/(x-1)]dy/dx=0,
∴1-u+(4+u)[u+(x-1)du/dx]=0,
∴u+(x-1)du/dx=(u-1)/(4+u),
∴(x-1)du/dx=(u-1)/(4+u)-u=(u-1-4u-u^2)/(4+u),
∴[(4+u)/(u^2-3u+1)]du=[1/(1-x)]dx,
∴[(2u-3+11)/(u^2-3u+1)]du=2d|1-x|,
∴2ln|1-x|=∫[(2u-3)/(u^2-3u+1)]du+11∫[1/(u^2-3u+1)]du,
∴2ln|1-x|=∫∫[1/(u^2-3u+1)]d(u^2-3u+1)+11∫[1/(u^2-3u+1)]du,
∴2ln|1-x|=ln|u^2-3u+1|+11∫{1/[(u-3/2)^2-5/4]}du,
∴2ln|1-x|=ln|u^2-3u+1|+11∫{1/[(u-3/2+√5/2)(u-3/2-√5/2)]du,
∴2ln|1-x|=ln|u^2-3u+1|
+(11/√5)∫[1/(u-3/2-√5/2)-1/(u-3/2+√5/2)]du,
∴2ln|1-x|=ln|u^2-3u+1|+(11/√5)ln|u-3/2-√5/2|
-(11/√5)ln|u-3/2+√5/2|+C,
∴2ln|1-x|
=ln|y^2/(x-1)^2-3y/(x-1)+1|+(11/√5)ln|y/(x-1)-3/2-√5/2|
-(11/√5)ln|y/(x-1)-3/2+√5/2|+C。
∴原微分方程的通解是:
2ln|1-x|
=ln|y^2/(x-1)^2-3y/(x-1)+1|+(11/√5)ln|y/(x-1)-3/2-√5/2|
-(11/√5)ln|y/(x-1)-3/2+√5/2|+C。